Patterns of Middle-Class Communities Adaptation to the Village SDGS Program in Bogor Regency - Isnaeni, Nur Meily; Dulkiah, Moh; Wildan, Asep Dadan (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2022)
Village is the smallest territorial space in Indonesia with a complex socio-economic problem. For this reason, the village SDGs was born as a micro-based global development agenda expected to realize village development efficiently. This program has the main objective of â€œNo One Left Behindâ€ with 18 main objectives that cover all levels of society. Among the best ideas in the 18 goals, the conclusion is still focused on sustainable village development through eradicating lower-class social issues with upper-class support. Then the question arises,